2017
DOI: 10.3389/fneur.2017.00526
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Associations between Headache and Gastrointestinal Disorders: A Study Using the Hallym Smart Clinical Data Warehouse

Abstract: BackgroundThe brain and gastrointestinal (GI) tract are strongly connected via neural, endocrine, and immune pathways. Previous studies suggest that headaches, especially migraines, may be associated with various GI disorders. However, upper GI endoscopy in migraineurs has shown a low prevalence of abnormal findings. Also, the majority of studies have not demonstrated an association between Helicobacter pylori (HP) infection and migraine, although a pathogenic role for HP infection in migraines has been sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…31 Lee, et al in a study used the clinical data warehouse method to analyze data regarding patients with different types of headaches and showed non-significant findings in keeping with higher prevalence of H. pylori contamination among migraine patients. 32 Faraji, et al in a double-blind clinical trial on 64 patients with migraine showed that H. pylori eradication caused a significantly larger decrease in the MIDAS score in contrast to the control group receiving placebo. 15 Doulberis, et al in a recent literature review demonstrated a higher prevalence of GI presentations among patients with migraine, although a clear pathophysiology remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…31 Lee, et al in a study used the clinical data warehouse method to analyze data regarding patients with different types of headaches and showed non-significant findings in keeping with higher prevalence of H. pylori contamination among migraine patients. 32 Faraji, et al in a double-blind clinical trial on 64 patients with migraine showed that H. pylori eradication caused a significantly larger decrease in the MIDAS score in contrast to the control group receiving placebo. 15 Doulberis, et al in a recent literature review demonstrated a higher prevalence of GI presentations among patients with migraine, although a clear pathophysiology remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Migraines are associated with various GI disorders, such as gastroparesis, GERD, irritable bowel syndrome, and celiac disease [ 12 , 13 , 14 ], and also cooccur with GI symptoms such as diarrhea, constipation, and dyspepsia [ 15 , 16 ]. A previous web-based survey, and a large CDW study of migraine patients, reported GERD prevalence rates of 22% and 27%, respectively [ 14 , 40 ]. Another clinic-based study reported that the prevalence of GERD was higher in migraineurs than non-migraineurs (42% vs. 18%) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dataset analyzed in the current study was acquired from the common integrated electronic CDW system of Hallym University Medical Center (HUMC) [14]. The common CDW system of HUMC collects and stores extensive electronic medical data including medical records, laboratory results, physical measurements, diagnostic and therapeutic history, and medication history, over a period of 10 years from the five branch hospitals of HUMC [14].…”
Section: Methodsmentioning
confidence: 99%